Copyright Protection Against Acts of Book Piracy (Reviewed from Shopee Sales) - Putwi Rindiani; Nariza Isandra; Lelya Cahya Mufidati; Gresnia Himbi Parkitasari (Universitas Muhammadiyah Surakarta, 2024)
The economic sector is presently undergoing a substantial transition, the range of traditional and online channels for buying and selling transactions has increased due to the ongoing development of digital innovation. Research from SIRCLO and Katadata Insight Center (KIC) indicates that a considerable proportion of consumers are now making purchases online, which highlights the need for efficient security measures to be put in place as soon as possible. One of the main functions of Undang-Undang Hak Cipta, namely Undang-Undang Nomor 28 Tahun 2014, is to provide a legal framework that governs electronic transactions and copyright. However, there are still a lot of obstacles to overcome before this rule may be put into practice in the context of electronic commerce. One of them is the general lack of knowledge among consumers and business actors about their responsibilities and rights when doing business online. One blatant instance of copyright violation in electronic commerce is book piracy. This situation frequently arises on websites like Shopee, where pirated books are offered for sale at far cheaper costs than the legitimate retail price. Furthermore, legitimate writers and publishers may suffer ethically and financially as a result of book piracy. Collaboration between the government, corporate players, and consumers is necessary to address the issues of copyright violations in electronic transactions and book piracy. Strict adherence to the law and heightened legal consciousness among companies and customers can successfully curb pirate activities and safeguard copyright.